Collateral in Loan Classification and Provisioning - Song, In (IMF Working Papers; Working Paper ;, 2002)
Adequate loan classification practices are an essential part of a sound and effective credit risk-management process in a bank. Failure to identify deterioration in credit quality in a timely manner can aggravate and prolong the problem. Two key issues arise with regard to the use of collateral in the context of loan classification and provisioning. In particular, the questions arise whether collateral should be taken into account in classifying a collateralized loan, and whether it should be considered in calculating provisions. This paper surveys country practices in the role of collateral in loan classification and provisioning, and suggests good practices on these issues.